Reduced hysteresis in La0.7Ce0.3Fe11.5Si1.5 hydrides by grain size reduction - Mitali Madhusmita Prusty; Sri Harsha Molleti; Hiroto Takanobu; Sai Rama Krishna Malladi; Xin Tang; Hossein Sepehri-Amin (Science and Technology of Advanced Materials)
Magnetic cooling technology, based on the magnetocaloric effect (MCE), offers an energy-efficient and eco-friendly alternative to conventional gas compression, but is often hindered by large magnetic hysteresis, which limits cyclic performance. In this study, we show that the hysteresis of La0.7Ce0.3(Fe,Si)₁₃ hydrides – a promising material for room-temperature refrigeration – can be significantly reduced by refining the microstructure of the precursor alloy. Substituting Ce for La in (La0.7Ce0.3)(Fe,Si)13Hx increases hysteresis losses from 12.3 J/kg to 34 J/kg. However, preparing the precursor alloy using the melt-spinning technique can almost eliminate this hysteresis. Lorentz transmission electron microscopy (Lorentz-TEM) shows that phase transition nucleation preferentially occurs at the grain boundaries. The hydrides prepared from melt-spun ribbons exhibit a much larger volume fraction of grain boundaries due to finer grains, providing a higher density of nucleation sites. This reduces the energy barrier for the phase transition and weakens the magneto-structural phase transition, as confirmed by in-situ X-ray diffraction patterns. Consequently, the reduced phase transition energy barrier leads to significantly lower hysteresis in melt-spun hydrides samples. These findings demonstrate the potential of microstructure engineering to reduce hysteresis in (La,Ce)(Fe,Si)13Hₓ materials for room-temperature magnetocaloric applications.